2007
DOI: 10.1177/1045389x07084149
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Evaluation Criteria of Piezoelectric Motors

Abstract: In this article, four types of piezoelectrically driven motors are evaluated: linear, horn-type, unidirectional rotary, and bidirectional traveling wave. Experimental results for velocity, power, and specific power are presented as a function of mechanical load. Analytical and experimental energy densities are compared based upon applied electrical potential. The bidirectional ultrasonic motor exhibited 34% of its available energy density, while the other motors produced values ranging from 0.63 to 9.5% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…While these motors have produced significant power outputs for their size, the mechanical translation through friction has limited power output. Tieck et al (2007) measured the intrinsic piezoelectric material power densities and compared them to the ultrasonic motor that utilized them. The intrinsic piezoelectric power densities ranged from 6.53 to 4500 W/kg, while the actual power densities of the motors spanned from 0.82 to 85.73 W/kg.…”
Section: Introductionmentioning
confidence: 99%
“…While these motors have produced significant power outputs for their size, the mechanical translation through friction has limited power output. Tieck et al (2007) measured the intrinsic piezoelectric material power densities and compared them to the ultrasonic motor that utilized them. The intrinsic piezoelectric power densities ranged from 6.53 to 4500 W/kg, while the actual power densities of the motors spanned from 0.82 to 85.73 W/kg.…”
Section: Introductionmentioning
confidence: 99%
“…One appealing embodiment of the vast literature on smart systems is the use of piezoelectric bimorphs since they offer various benefits over other designs such as the piezoelectric ultrasonic wave motors. For example, the bimorph motors provides high output power for a given torque and requires lower applied electric field (Tieck et al, 2007). Furthermore, the bimorph motors are generally very stiff and stable enabling very accurate load positioning with accuracies which are in the neighborhood of 10 nm (http://www.piezomotor.se/).…”
mentioning
confidence: 99%
“…Furthermore, the bimorph motors are generally very stiff and stable enabling very accurate load positioning with accuracies which are in the neighborhood of 10 nm (http://www.piezomotor.se/). However, these performance metrics occur at the expense of higher motor weight, low travel speeds, and low overall efficiency (Tieck et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tieck et al demonstrated that the use of friction to rectify piezoelectric strain effectively reduces the total power output that is transmitted from the high density piezoelectric actuator to the load [5]. Electrohydraulic pumps use an incompressible fluid and two one-way valves to convert the small displacements of an electroactive stack actuator into a continuous flow of pressurized fluid for mechanical work.…”
Section: Introductionmentioning
confidence: 99%